2016
DOI: 10.1002/mus.25205
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting outcome in myasthenia gravis

Abstract: Prognosis is favorable for the majority of MG patients, regardless of age, maximum disease severity, or antibody status. Muscle Nerve, 2016 Muscle Nerve 54: 1041-1049, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
5
45
1
1
Order By: Relevance
“…Early aggressive treatment of MG using conventional approaches, followed by lower doses of oral corticosteroids, appears to be a worthwhile strategy in reaching favorable long‐term outcomes. The current findings bolster other recent reports that demonstrate the feasibility of tapering, albeit slowly, other immunosuppressive agents in MG without compromising disease control . As always, a prospective study testing such treatment principles would be ideal, but in the meantime the weight of retrospective evidence is certainly something to consider when making early treatment decisions in MG.…”
supporting
confidence: 76%
“…Early aggressive treatment of MG using conventional approaches, followed by lower doses of oral corticosteroids, appears to be a worthwhile strategy in reaching favorable long‐term outcomes. The current findings bolster other recent reports that demonstrate the feasibility of tapering, albeit slowly, other immunosuppressive agents in MG without compromising disease control . As always, a prospective study testing such treatment principles would be ideal, but in the meantime the weight of retrospective evidence is certainly something to consider when making early treatment decisions in MG.…”
supporting
confidence: 76%
“…This result is consistent with results from previous studies that included large numbers (>100) of patients . However, other studies have found that nonthymomatous pathology is not a prognostic factor . This discrepancy may be a result of differences in participants, follow‐up times, or sample sizes.…”
Section: Discussionmentioning
confidence: 84%
“…4,6,15 However, other studies have found that nonthymomatous pathology is not a prognostic factor. 5,[16][17][18] This discrepancy may be a result of differences in participants, followup times, or sample sizes. The latter studies included <100 MG patients with thymoma.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is symptomatic with an acetylcholine esterase inhibitor, immunosuppression and thymectomy . With optimal therapy most patients have only mild symptoms or remission . MG crisis with impaired respiratory function and need of intensive care remains a threat.…”
Section: Myasthenia Gravis In Reproductive Agementioning
confidence: 99%